Dynamic Angular Petrissage as Treatment for Axillary Web Syndrome Occurring after Surgery for Breast Cancer: a Case Report - Lewis, BA, RMT, CDT, Paul A.; Cunningham, PhD, Joan E. (International Journal of Therapeutic Massage & Bodywork, 2016)
Background: In the context of breast cancer, axillary web syndrome (AWS), also called lymphatic cording, typically presents in the weeks after axillary surgery. This painful condition, likely lymphofibrotic in origin, restricts upper extremity range of motion (ROM). There is no established treatment, although physical therapy and other approaches have been used to variable effect. This report describes treatment of a female client with AWS, who had recently undergone a unilateral simple mastectomy with sentinel node biopsy plus axillary dissection. Methods: The client presented with pain upon movement (self-reported as 5 on the 0–10 Oxford Pain Scale), visible cording and restricted use of the ipsilateral upper extremity. Clinical assessment included determining the extent of AWS cording (taut, from axilla to wrist) and measuring glenohumeral joint ROM (140° flexion by goniometer). A therapeutic massage with movement protocol, termed dynamic angular petrissage, was administered over two sessions: Swedish massage combined with dynamically taking the limb through all possible angles of movement (passive ROM), controlling stretch and tension while simultaneously and segmentally applying petrissage and non-petrissage techniques to the underlying soft tissue. Careful attention was taken to not break the cord. Home care consisted of prescribed exercises performed by the patient. Results: After Session One, pain was reduced (to 0/10), ROM improved (to 170° flexion), and cording was visibly reduced. After Session Two the cord was residually apparent only on hyperextension, with no ROM restrictions in glenohumeral joint flexion. Follow-up at three months revealed absence of visual or palpable evidence of cording, unrestricted glenohumeral joint ROM, and absence of movement-associated pain. Conclusion: The signs and symptoms of AWS were quickly and effectively eliminated, without causing any pain or discomfort to the client. We propose that dynamic angular petrissage may be an efficient and safe treatment approach for reducing the pain, mobility restrictions, and cording of AWS.